2021
DOI: 10.21203/rs.3.rs-514812/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy-enhanced and cytokine release syndrome-attenuated anti-CD7 universal chimeric antigen receptor-T cell therapy for relapsed/refractory CD7-positive hematological malignancies: A phase I clinical study

Abstract: Chimeric antigen receptor-T cell (CAR-T) therapy in T cell malignancies faces fratricide, T cell aplasia, and product contamination. Here, we successfully developed a universal anti-CD7 CAR-T product (RD13-01). RD13-01 contains a bbzg-CAR comprising an anti-CD7 single-chain variable fragment, a 4-1BB costimulatory domain, a CD3ζ signaling domain, the intracellular domain of the common γ chain, and a natural killer cell inhibitory molecule (E-cadherin). TRAC, CD7 and HLA-II were disrupted to avoid graft versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The short persistence is considered to be an advantage to prevent T-cell aplasia but also a disadvantage to prevent cancer recurrence 3 . Interestingly, less than 4 weeks of CAR-T cell persistence is adequate for majority of patients to reach MRD-CR in both studies 20 . 3 patients treated with GC027 maintained PFS > 6 months with a single infusion (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The short persistence is considered to be an advantage to prevent T-cell aplasia but also a disadvantage to prevent cancer recurrence 3 . Interestingly, less than 4 weeks of CAR-T cell persistence is adequate for majority of patients to reach MRD-CR in both studies 20 . 3 patients treated with GC027 maintained PFS > 6 months with a single infusion (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Theoretically, the likelihood of CAR + leukemia cells in autologous CAR-T products is higher in T malignancies, especially with approaches to reduce fratricide. Huang at al have recently reported clinical data on a similar allogeneic, universal CD7 CAR-T approach to GC027, but the two products were enhanced by different cytokine receptors 20 . Huang et al introduced a γc portion to the CAR intracellular domain and observed rescue of IL-2 production and enhanced proliferation20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations